2022
DOI: 10.3389/fonc.2022.933675
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Resistance to Anticancer Drugs: A Tumor Skeleton Key for Unhinging Chemotherapies

Abstract: Although surgical procedures and clinical care allow reaching high success in fighting most tumors, cancer is still a formidable foe. Recurrence and metastatization dampen the patients’ overall survival after the first diagnosis; nevertheless, the large knowledge of the molecular bases drives these aspects. Chemoresistance is tightly linked to these features and is mainly responsible for the failure of cancer eradication, leaving patients without a crucial medical strategy. Many pathways have been elucidated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 179 publications
0
3
0
Order By: Relevance
“…Nevertheless, an increase in average number EVs in drug treated vin tolerant lines was observed, which can be further supported with literature, where it has also indicated that EVs can act as transporters for efflux of drugs. 23 Thus it can be concluded that number of EVs are enhanced in drug tolerant lines which together with EC50 data suggest EV mediated drug tolerance in medulloblastoma cell lines.…”
Section: Drug Resistance In Medulloblastomasmentioning
confidence: 85%
“…Nevertheless, an increase in average number EVs in drug treated vin tolerant lines was observed, which can be further supported with literature, where it has also indicated that EVs can act as transporters for efflux of drugs. 23 Thus it can be concluded that number of EVs are enhanced in drug tolerant lines which together with EC50 data suggest EV mediated drug tolerance in medulloblastoma cell lines.…”
Section: Drug Resistance In Medulloblastomasmentioning
confidence: 85%
“…It exerts its anti-fibrotic effects by antagonizing TGFβ-induced EMT and promoting tissue repair and regeneration. GED-0507-34 Levo is an orally active synthetic compound and a selective agonist of PPARγ that has been shown to inhibit EMT, reduce inflammation, and ameliorate fibrosis in a DSS model (Di Gregorio et al, 2017;Pompili et al, 2023). In fact, GED-0507-34 is in a Phase 2 clinical trial in subjects with active, mild-tomoderate UC (ClinicalTrials.gov Identifier: NCT02808390).…”
Section: Proteinmentioning
confidence: 99%
“…Furthermore, ADM-resistant cell-derived sEVs endow sensitive cells with a drug-resistant phenotype [ 76 ]. Evidence shows that drug-resistant tumor cells gain chemoresistance by encasing chemotherapeutic drugs into sEVs and excreting them [ 169 , 170 ]. sEVs contain a large amount of genetic material and are exchanged among cells in TME.…”
Section: Tumor-derived Sevs Play Vital Roles In the Bc Microenvironmentmentioning
confidence: 99%